Climate change : observed impacts on planet Earth - Letcher, T. M. (Trevor M.) (Elsevier, 2009)
The climate of the Earth is always changing. As the debate over the implications of changes in the Earth's climate has grown, the term climate change has come to refer primarily to changes we've seen over recent years and those which are predicted to be coming, mainly as a result of human behavior. This book serves as a broad, accessible guide to the science behind this often political and heated debate by providing scientific detail and evidence in language that is clear to both the non-specialist and the serious student. * provides all the scientific evidence for and possible causes of climate change in one book * written by expert scientists working in the field * logical, non-emotional conclusions * a source book for the latest findings on climate change.